Making sense of ICD-11 diagnostic criteria of compulsive sexual behavioural disorder - Syidda Amron; Kandasami Gomathinayagam; Cheng Lee; Song Guo; Hui Shan Tan (Annals, Academy of Medicine, Singapore)
Compulsive sexual behaviour disorder (CSBD) is identified by persistent, intense sexual urges that lead to repetitive activities, causing significant distress or impairment over 6 months or more.1 It is characterised by neglecting important responsibilities, repeated unsuccessful attempts to control the behaviour and continuation despite negative consequences.1 Crucially, the distress linked to CSBD is not due to moral judgments about sexual behaviour.1